Penguatan Peran Masyarakat Menuju Kemandirian Kesehatan Melalui Pemanfaatan Tanaman Obat Keluarga (Toga) dalam Pengendalian Penyakit Kolesterol - Recky Patala; I Made Sarwadana; Tri Olan Palumpun; Ayu Wulandari (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
Efforts towards the independence of health human resources are a concrete manifestation of community participation in health development as a trigger for community empowerment activities, one of which is Family Medicinal Plants (FMP). FMP is a selection of medicinal plants that can be planted in the home yard. The utilization of Family Medicinal Plants in controlling Cholesterol Disease in the home environment is very important, especially for families who do not have access to health services. Therefore, this activity aims to help and strengthen the role of the community, especially the Prosperous Village community in utilizing FMP around as an alternative medicine for controlling Cholesterol Disease. The methods used in the implementation of this service are observation, preparation and design, socialization, lectures, discussions, and training and mentoring. The results achieved from this activity are an increased understanding of the types of FMP, their classification, processing methods, utilization of FMP, and the importance of FMP for cholesterol treatment and getting FMP cultivation skills by utilizing the yard and garden around the house to be used as a place for FMP cultivation. The existence of a FMP garden which is the output of this service is then expected to be used for treatment or can be used to improve the economy by selling FMP products.